RNA m6A Demethylase ALKBH5 Protects Against Pancreatic Ductal Adenocarcinoma via Targeting Regulators of Iron Metabolism - Huang, Rui; Yang, Lin; Zhang, Zhiwen; Liu, Xiaoding; Fei, Yi; Tong, Wei-Min; Niu, Yamei; Liang, Zhiyong (Frontiers in Cell and Developmental Biology, 2021)
Although RNA m6A regulators have been implicated in the tumorigenesis of several different types of tumors, including pancreatic cancer, their clinical relevance and intrinsic regulatory mechanism remain elusive. This study analyzed eight m6A regulators (METTL3, METTL14, WTAP, FTO, ALKBH5 and YTHDF1-3) in pancreatic ductal adenocarcinoma and found that only RNA m6A demethylase ALKBH5 serves as an independent favorable prognostic marker for this tumor. To better understand the molecular mechanism underlying the protective effect conferred by ALKBH5 against pancreatic tumorigenesis, we performed a transcriptome-wide analysis of m6A methylation, gene expression, and alternative splicing using the MIA PaCa-2 stable cell line with ALKBH5 overexpression. We demonstrated that ALKBH5 overexpression induced a reduction in RNA m6A levels globally. Furthermore, mRNAs encoding ubiquitin ligase FBXL5, and mitochondrial iron importers SLC25A28 and SLC25A37, were identified as substrates of ALKBH5. Mechanistically, the RNA stabilities of FBXL5 and SLC25A28, and the alternative splicing of SLC25A37 were affected, which led to their upregulation in pancreatic cancer cell line. Particularly, we observed that downregulation of FBXL5 in tumor samples correlated with shorter survival time of patients. Owing to FBXL5-mediated degradation, ALKBH5 overexpression incurred a significant reduction in iron-regulatory protein IRP2 and the modulator of epithelial-mesenchymal transition SNAI1. Notably, ALKBH5 overexpression led to a significant reduction in intracellular iron levels as well as cell migratory and invasive abilities, which could be rescued by knocking down FBXL5. Overall, our results reveal a previously uncharacterized mechanism of ALKBH5 in protecting against pancreatic ductal adenocarcinoma through modulating regulators of iron metabolism and underscore the multifaceted role of m6A in pancreatic cancer.